2020
DOI: 10.1001/jama.2019.20079
|View full text |Cite
|
Sign up to set email alerts
|

Association of Powder Use in the Genital Area With Risk of Ovarian Cancer

Abstract: Importance:The relationship between genital powder use and ovarian cancer is not established. Positive associations reported in case-control studies have not been confirmed in cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…[ 182 ]. Apart from the contamination of talc with asbestos until the end of the 1970s and beyond [ 183 , 184 ], the presence of tainted talc in commercially available powder formulations has varied over time in various brands of products, resulting in difficulties for epidemiological studies to define an ascertained genital talc exposure [ 185 ] and to avoid statistical bias [ 186 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 182 ]. Apart from the contamination of talc with asbestos until the end of the 1970s and beyond [ 183 , 184 ], the presence of tainted talc in commercially available powder formulations has varied over time in various brands of products, resulting in difficulties for epidemiological studies to define an ascertained genital talc exposure [ 185 ] and to avoid statistical bias [ 186 ].…”
Section: Discussionmentioning
confidence: 99%
“…The type and number of fibers that could potentially be inhaled during normal use of talcum powder were found to be superimposable on those detected in the lung tissue of a woman who died of mesothelioma. The debate sparked by this paper led to several works focusing on this topic until last year with controversial results [ 35 , 37 , 184 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 ]. For example, it should be emphasized that no excesses of pleural mesothelioma nor talc pneumoconiosis were found in studies of miners in talc mines [ 177 , 225 , 226 , 227 , 228 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the use of powdered talc in the genital area. This chemical may alter the microenvironment subsequently elevating the risk of cancer [ 47 ]. Finally, in observational studies patients with ovarian cancer or predisposition for ovarian cancer (germline BRCA1 mutation) were associated with a specific microbiome in the vagina/cervix [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unconvincing data have been obtained for the association between powder use in the genital area and the risk of ovarian cancer. In this context, some studies highlighted a slightly increased risk of ovarian cancer in women using talc powder in the genital area ( 28 - 30 ). However, a recent observational study on 250,000 women observed for 11 years has demonstrated that the use of powder does not significantly increase the incidence of ovarian cancer ( 28 - 30 ).…”
Section: Risk and Protective Factors For Ovarian Cancermentioning
confidence: 99%